Achieving Uniform Monolayer Transition Metal Dichalcogenides Film on Silicon Wafer via Silanization Treatment: A Typical Study on WS2. Issue 7 (14th December 2016) - Chen, Ying; Gan, Lin; Li, Huiqiao; Ma, Ying; Zhai, Tianyou
Abstract : A silanization reaction is employed to improve the dispersion of precursors on a silicon wafer for a large‐size uniform transition metal dichalcogenide (TMD) film synthesis and to achieve a highly crystalline monolayer WS2 film up to 1 cm 2 . The novel strategy is also verified for the synthesis of WSe2 and MoS2 uniform films, suggesting universality for TMD film fabrication.